Process-Structure-Properties in Polymer Additive Manufacturing - Sing, Swee Leong; Yeong, Wai Yee (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Additive manufacturing (AM) methods have grown and evolved rapidly in recent years. AM for polymers is an exciting field and has great potential in transformative and translational research in many fields, such as biomedical, aerospace, and even electronics. Current methods for polymer AM include material extrusion, material jetting, vat polymerisation, and powder bed fusion. With the promise of more applications, detailed understanding of AM-from the processability of the feedstock to the relationship between the process-structure-properties of AM parts-has become more critical. More research work is needed in material development to widen the choice of materials for polymer additive manufacturing. Modelling and simulations of the process will allow the prediction of microstructures and mechanical properties of the fabricated parts while complementing the understanding of the physical phenomena that occurs during the AM processes. In this book, state-of-the-art reviews and current research are collated, which focus on the process-structure-properties relationships in polymer additive manufacturing.